LOGISTICS IS A FACTOR FOR THE DEVELOPMENT OF AGRICULTURAL INDUSTRY - Madaliyev, Abdulla Ahmedovich; Khalikov, Suyun Ravshanovich (The journal of contemporary issues in business and government, 2021)
The article provides scientific proposals and practical recommendations on the role of logistics in the implementation of innovative and economic changes in the agro-industrial sector of the country as well as the implementation of the Strategy of Agricultural Development of the Republic of Uzbekistan for 2020-2030.